IMPLEMENTASI PEMBELAJARAN RINTISAN SEKOLAH BERTARAF INTERNASIONAL (RSBI) PADA SEKOLAH DASAR NEGERI (SDN) NOMOR 55 DI KOTA BIMA - Ardi, Ardi (Jurnal Studi Agama dan Masyarakat, 2010)
This research aims to find out (1) the learning implementation conducted by the international level pioneering school in SDN no. 55 of Bima city, (2) to reveal the advantage dimension the international level pioneering school has in SDN no. 55 of Bima city, and (3) to find out the factor inhibiting and the solution in the learning implementation of the international level pioneering school in SDN no. 55 of Bima city. This research is a study using qualitative approach. The data source obtained derived from (1) event, (2) actor, and (3) document. Techniques of collecting data used were (1) interview, (2) observation and (3) documentation. The data validity testing was done using: data source triangulation, member checking, peer discussion. The result of research was analyzed using an interactive qualitative model encompassing (1) data collection period, (2) data reduction (3) conclusion and data verification.The conclusions of research result are (1) the implementation of international level school pioneering learning in SDN No 55 of Bima city: (a) accredited on may 24,2008 with B value.(b)the curriculum used by SDN No 55 of Bima city is still national curriculum (KTSP) with the expansion consistent with the student requirement (c) learning using Indonesia for grade 1 to 3 and English for grade 4 to 6 as the delivery language despite not maximally. In addition, only few teachers use learning media because of limited teacher human resource. (d) the educators are given opportunity to continue their study for teacher and lecturer act as well as to attend English course and computer training corresponding to the schedule predefined by school. (e) the infrastructure has been very sporting for the teaching learning activity such as language and computer laboratories.(f) the assessment is done by the teacher giving assignment to the students to work on at home such memorizing prayers and teachers will do assessment at scholl (g) the students is selected tightly in the new students admission according to the criteria predefined by the school.(i)the fund derivers from BOS fund as well as imposed to the student per month consistent with the agreement among the committee, student parents and school (2) the advantage of SDN no.55 of Bima city lies in the achievement reached by the students, both academic and non academic, achieved through many activities both in municipal and in province levels. In addition, the advantage also lies in the very adequate infrastructure for the teaching-learning activity; (3) the obstacles encountered by SDN No.55 of Bima city include the limitedness human resource among the teachers and students both in English communication and in the use of learning media. In addition, the fund factor really inhibits the teaching-learning activity.